The Formation of Aufeis and Its Impact on Infrastructure around Ulaanbaatar, North-Central Mongolia - Walther, Michael; Batsaikhan, Vanchindorj; Dashtseren, Avirmed; Jambaljav, Yamkhin; Temujin, Khurelbaatar; Ulanbayar, Ganbold; Kamp, Ulrich (DigitalCommons@University of Nebraska - Lincoln, 2021)
In this study aufeis features and their formation under natural conditions and in an urban surrounding in north-central Mongolia were investigated. Used methods included field observations, Electrical Resistivity Tomography (ERT) as well as analyses of satellite imagery and meteorological data. Aufeis formation is related to streams, springs, and ground conditions, particularly soil moisture; the formation of both spring aufeis and river aufeis follows a seasonal cycle. The meteorological data from 1969 to 2018 indicate that the mean annual air temperature (MAAT) increased by 2.6 °C, whilst no significant changes were observed for precipitation. Between 1992 and 2018, aufeis areas significantly decreased at all sites, which is likely caused by the air temperature increase. In urban environments, aufeis and its meltwater can damage infrastructure and lead to soil and water pollution. Therefore, urban planning strategies in northern Mongolian settlements should be concerned with aufeis occurrence.